2022
DOI: 10.1038/s41598-022-06648-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gastrointestinal digestion of Lentinus squarrosulus powder and impact on human fecal microbiota

Abstract: Humans have long-used mushrooms as food and medicine, but digestion and colonic fermentation of most mushrooms, including Lentinus squarrosulus is markedly unknown. Here, nutritional profile, digestion and colonic fermentation of L. squarrosulus powder (LP) were determined. The powder contained mainly carbohydrate and protein. SEM and F-TIR analysis of the resistant hydrolysate (RH) revealed that the structure and ratio of carbohydrate and protein components were altered, and released known immunomodulation ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Crude protein ranged from 6.60 to 30.69 g/100 g among mushrooms obtained from the Kilum-Ijim forest in Cameroon [ 7 ]. Lentinus squarrosulus powder presented an excellent protein value of 30.12 g/100 g [ 11 ]. Even though the whole fruiting body of a mushroom is commonly consumed, it is interesting to note that different parts of the mushroom present different protein values.…”
Section: Nutritional Value Of Edible Mushroom Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Crude protein ranged from 6.60 to 30.69 g/100 g among mushrooms obtained from the Kilum-Ijim forest in Cameroon [ 7 ]. Lentinus squarrosulus powder presented an excellent protein value of 30.12 g/100 g [ 11 ]. Even though the whole fruiting body of a mushroom is commonly consumed, it is interesting to note that different parts of the mushroom present different protein values.…”
Section: Nutritional Value Of Edible Mushroom Proteinsmentioning
confidence: 99%
“…Concurrently, unhydrolyzed protein may improve health by stimulating the gut microbiota as revealed in previous studies. Ayimbila et al found that simulated gastro-intestinal digestion of L. squarrosulus powder resulted in 58.59% of its protein hydrolyzed in gastric condition and only reached 59.59% after hydrolysis in intestinal condition [ 11 ]. Protein profile and digestibility of G. lingzhi (GZ) and G. lucidum (GL)-Madrid mushroom proteins in simulated gastric fluid differ significantly.…”
Section: The Biological Role Of Mushroom Proteins In Human Dietmentioning
confidence: 99%
See 3 more Smart Citations